Melatonin Alleviates Radiation-Induced Lung Injury via Regulation of miR-30e/NLRP3 Axis. (10th January 2019) - Wu, Xu; Ji, Haiying; Wang, Yuli; Gu, Chenlin; Gu, Wenyu; Hu, Lijuan; Zhu, Lei
Abstract : Melatonin is a well-known anti-inflammatory and antioxidant molecule, which plays a crucial role in various physiological functions. In this study, mice received a single dose of 15 Gy radiation delivered to the lungs and daily intraperitoneal administration of melatonin. After 7 days, mice were processed to harvest either bronchoalveolar lavage fluid for cytokine assays or lungs for flow cytometry and histopathological studies. Herein, we showed that melatonin markedly alleviated the oxidative stress and injury, especially suppressing the infiltration of macrophages (CD11b+CD11c−) and neutrophils (CD11b+Ly6G+) to the irradiated lungs. Moreover, in the irradiated RAW 264.7 cells, melatonin blocked the NLRP3 inflammasome activation accompanied with the inhibition of the IL-1 β release and caspase-1 activity. However, melatonin restored the downregulated miR-30e levels. Quantitative PCR analysis of miR-30e and NLRP3 indicated the negative correlation between them. Notably, immunofluorescence staining showed that overexpression of miR-30e dramatically diminished the increased NLRP3 expression. Luciferase reporter assay confirmed that NLRP3 was a target gene of miR-30e. Western blotting revealed that transfection with miR-30e mimics markedly reduced the expressions of NLRP3 and cleaved caspase-1, whereas this phenomenon was reversed by the miR-30e inhibitor. Consistent with this, the beneficial effect of melatonin under irradiated exposure was blunted in cells transfected with anti-miR-30e. Collectively, our results demonstrate that the NLRP3 inflammasome contributed to the pathogenesis of radiation-induced lung injury. Meanwhile, melatonin exerted its protective effect through negatively regulating the NLRP3 inflammasome in macrophages. The melatonin-mediated miR-30e/NLRP3 signaling may provide novel therapeutic targets for radiation-induced injury.